2009
DOI: 10.1248/bpb.32.619
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Monkey Embryonic Stem Cells into Hepatocytes and mRNA Expression of Cytochrome P450 Enzymes Responsible for Drug Metabolism: Comparison of Embryoid Body Formation Conditions and Matrices

Abstract: Examination of drug metabolism using human hepatocytes is important in the early stages of drug development. However, primary human hepatocytes are short-lived and cannot be maintained in culture over the long term. Considerable donor-dependent variations are also problematic. Human embryonic stem (ES) cells are pluripotent cells derived from the inner cell mass of blastocysts and are capable of differentiating into three embryonic germ layers and germ cells.1) The cells apparently differentiate into various t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…The effects of RIF on mRNA expression of cmCYP3A4 (3A8) in the cmESC-derived hepatic cells was consistent with the findings reported previously. 7) It was previously reported that cmCYP3A4 (3A8) is induced by RIF through the transcription factor PXR. 29) Our study showed that PXR is expressed in cmESC-derived hepatic cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The effects of RIF on mRNA expression of cmCYP3A4 (3A8) in the cmESC-derived hepatic cells was consistent with the findings reported previously. 7) It was previously reported that cmCYP3A4 (3A8) is induced by RIF through the transcription factor PXR. 29) Our study showed that PXR is expressed in cmESC-derived hepatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…18) This method was applied to the induction of differentiation of monkey ESCs into hepatic cells. 7) In recent studies, however, a method to add some direct inducing factors to a monolayer culture system of an undifferentiated ESC colony without EB formation has been used extensively. Furthermore, some improved methods for more efficient differentiation into hepatocytes have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To achieve this goal, researchers have successfully exploited the molecular signals for liver development outlined above to direct the development of mouse (19 -21) and subsequently monkey (22,23) and human (24 -30) ESCs into hepatocyte-like cells (HLCs). Additionally, a few studies have demonstrated that mouse or monkey ESCs can be coaxed to generate HLCs in the presence of murine hepatocytes (31,32) or human liver nonparenchymal cells (33).…”
mentioning
confidence: 99%